Identification of highly potent and selective PI3Kδ inhibitors. Issue 13 (1st July 2017) - Marcoux, David; Qin, Lan-Ying; Ruan, Zheming; Shi, Qing; Ruan, Qian; Weigelt, Carolyn; Qiu, Hongchen; Schieven, Gary; Hynes, John; Bhide, Rajeev; Poss, Michael; Tino, Joseph
Graphical abstract: Abstract: Selective PI3Kδ inhibitors have recently been hypothesized to be appropriate immunosuppressive agents for the treatment of immunological disorders such as rheumatoid arthritis. However, few reports have highlighted molecules that are highly selective for PI3Kδ over the other PI3K isoforms. In this letter, isoform and kinome selective PI3Kδ inhibitors are presented. The Structural Activity Relationship leading to such molecules is outlined.